Mitology of the Tolak Angin Sido Muncul Advertisement by Rhenald Kasali Version (Semiotic Analysis of Roland Barthes) - Hermawan, Heri; Bakri, Wahyuddin (Jurnal Mercusuar, 2021)
The presence of myths shows how culture works and becomes the basis for human social and cultural life. The position of advertising in media texts is not only seen as something that is born to provide the function of the product, but there are also myths that spread in the content of the advertisement. This research aims to reveal the myths and ideologies in the content of the Sido Muncul advertisement version of Rhenald Kasali. This study uses Roland Barthes’ semiotics by dividing the analysis into three aspects, namely denotation, connotation, and myth, and the research approach in this thesis uses a qualitative research approach. The results show that the promoted product tends to work ideologically and appears natural in the human mind. The Tolak Angin advertisement works by reconstructing the meaning of a sacred and hygienic product that is only produced by sophisticated technology machines, and indicates the ideology of capitalism working and transferring social values ​​into products so that the product will mean something like taking the sign of Professor and attaching it to the product, so that the product means the same as Professor. The advertisement also gives meaning to humans through the products they consume by associating intelligent people when drinking the Tolak Angin advertisement product.